Rapid detection of avipoxvirus using a fluorescent probe-based multienzyme isothermal amplification assay - Zhu, Yinchu; Huo, Suxin; Chen, Liu; Fu, Yuan; Hua, Jionggang; Yun, Tao; Zhang, Cun; Ni, Zheng; Ye, Weicheng (Frontiers in Veterinary Science, 2025)
Avipoxvirus (APV) is a prevalent DNA virus in avian species, causing clinical symptoms of fowlpox and leading to reduced egg production, slower broiler growth, and increased mortality. The spread of APV poses a significant threat to the global poultry industry, potentially causing substantial economic losses. Effective control of APV, particularly its major species such as fowlpoxvirus and pigeonpoxvirus, requires the development of rapid and specific diagnostic tools. In this study, a novel multi-enzyme isothermal rapid amplification (MIRA) assay was developed to detect APV. Various primer-probe combinations were screened to identify an optimal pair targeting a conserved region of the viral P4b gene. The MIRA assay operates at a constant temperature and results can be visualized through fluorescence signal detection. The sensitivity, specificity, and applicability of the MIRA assay were evaluated. Additionally, 86 clinical samples were tested to assess the accuracy of the MIRA assay. The MIRA assay provides results within 15 minutes demonstrated high specificity, with no cross-reactivity with other avian pathogens. It achieved a detection limit of 50 copies/μl, which is consistent with the qPCR assay. Further evaluation with 86 clinical samples showed that the accuracy of the MIRA assay was comparable to that of qPCR in detecting fowlpoxvirus and pigeonpoxvirus. The results highlight the convenience, sensitivity, and rapidity of the MIRA assay as a promising tool for diagnosing APV.